A nutritional importance of school meals for the community (Research, Society and Development, 2021)
Introduction: The school lunch or simply lunch refers to the food that students have inside schools, especially during breaks, and is instituted in public schools in Brazil by the PNAE, created in a series from the 1950s. General objective: analyze importance of school meals for students. Methodology: The study was carried out with data collection from secondary sources, through a bibliographic survey and based on the authors' experience. Results and Discussion: the lunch, in addition to feeding and nourishing the children, also offers social interaction between schoolmates and the cooks. Teachers encourage the development of good eating habits and teach what it is like to sit at the table and eat in common. Final Considerations: The school lunch offered in public schools is important to the psychophysical development of the student, helping him in all aspects: physical motor, intellectual, emotional affective, economic and social. These aspects of well-being contribute to the subject having satisfactory conditions to learn.